Understanding Australian methylamphetamine drug markets through relational, temporal and spatial analyses. Issue 3 (2nd November 2021) - Popovic, Ana; Morelato, Marie; Baechler, Simon; De Grazia, Adrian; Tahtouh, Mark; Roux, Claude; Beavis, Alison
Abstract: In the area of illicit drugs, forensic case data have proven effective at detecting links between seizures and providing greater insights into illicit drug markets. This research explored the application of mathematical and statistical techniques to several chemical profiles of Australian methylamphetamine seizures. The main aim was to create and deliver a method that would expand the use of illicit drug profiling for strategic intelligence purposes, contributing to the fight against illicit drug trafficking. The use of comparison metrics and clustering analysis to determine links between existing illicit drug specimens and subsequent new specimens was evaluated and automated. Relational, temporal and spatial analyses were subsequently used to gain an insight into illicit drug markets. Relational analysis identified clusters of seizures central to the network. Temporal analysis then provided insights into the behaviour of distribution markets, specifically the emergence and extinction of certain clusters of seizures over time. Spatial analysis aided the understanding of the inter‐jurisdictional nature of illicit drug markets. These analyses allowed for the generation of strategic intelligence relating to when and where the Australian methylamphetamine illicit drug market was the most active. Additionally, the strategic level trends identified clusters of seizures that were worth investigating further. These clusters were explored through a case study, which exploited additional chemical profiling data to provide drug market knowledge at an operational level. In turn, the intelligence produced at various levels could allow relevant law enforcement agencies to take necessary measures in disrupting markets. Abstract : Relational analysis identified clusters of seizures central to the network. Temporal analysis provided insights into the behaviour of distribution markets, specifically the emergence and extinction of certain clusters of seizures over time. Spatial analysis aided the understanding of the inter‐jurisdictional nature of illicit drug markets.